2002
DOI: 10.1046/j.1365-2249.2002.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble p55 and p75 tumour necrosis factor-αreceptors in patients with hepatitis C-associated mixed cryoglobulinaemia

Abstract: SUMMARYTo investigate whether tumour necrosis factor a (TNFa) plays a role in the pathogenesis of hepatitis C virus-associated mixed cryoglobulinaemia (HCV-MC), we measured soluble TNFa and its soluble p55 (sTNFR1) and p75 (sTNFR2) receptors in the serum of patients with HCV-MC. TNFa, sTNFR1 and sTNFR2 were measured in the serum of 32 patients with HCV-MC, 18 patients with hepatitis C without MC (HCV) and 18 healthy volunteers, using specific immunoassays. Correlations between clinical and biological parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In patients presenting with HCV-MC vasculitis, IFN-a and ribavirin may exert their effects via inhibition of viral replication [34,35] rather than by complete eradication of the virus, or by an anti-inflammatory action [36][37][38]. The Th1/Th2 differentiation is critical in influencing liver disease progression in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients presenting with HCV-MC vasculitis, IFN-a and ribavirin may exert their effects via inhibition of viral replication [34,35] rather than by complete eradication of the virus, or by an anti-inflammatory action [36][37][38]. The Th1/Th2 differentiation is critical in influencing liver disease progression in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an increase in soluble TNFR-2 levels in cases of HBV infection is likely one of the pathways involved in HBV infection-related These data are also of interest for studies of cell death plasma analytes and MPs in cases of HBV and HCV infection. Both HBV and HCV are associated with hepatocyte apoptosis during stages in cases of chronic viral hepatitis infection (11,40,41,49). We found no significant elevations of plasma TRAIL, TNFR-2, or Fas ligand levels in HBV in comparisons of pre-T 0 with post-T 0 levels (Fig.…”
mentioning
confidence: 61%
“…MPs are small membrane-bound vesicles that are released from the surface of apoptotic cells by exocytic or budding processes; as such, MPs bear cell surface markers and can bind annexin V because of the expression of phosphatidylserine (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)39). MPs, which circulate in the blood under many clinical conditions, are part of a spectrum of subcellular structures that are released from cells and can be distinguished from exosomes, which are released from multivesicular bodies during activation.…”
Section: A Critical Event In Human Immunodeficiency Virus Type 1 (Hivmentioning
confidence: 99%
“…13 There is also convincing evidence that aPL can activate endothelial cells and monocytes in vivo and in vitro, and this activation can be demonstrated by the increased expression of different cellular adhesion molecules and tissue factor (TF). [24][25][26][27][28][29][30] The thrombotic tendency induced by aCL was reported to be related to the titer, but not the titers of anionic phospholipid antibodies. 15 This finding was also supported by an animal study which revealed a dose-dependent effect of white blood cell sticking to endothelial cells induced by aCL present in the sera of the mice.…”
Section: Immunopathology Of Apsmentioning
confidence: 99%